GHALIZUL QALB QUR’ANIC PERPECTIVE - Purwati, Heri; Firdaus; Basri, Halimah (Program Pascasarjana, UIN Alauddin Makassar, 2022)
This study is a study of ghalizul Qalb Perspectives of the Qur'an. The subject matter is